Pengembangan Gross Motorskill Anak Usia 7 Tahun Melalui Alat Peraga Edukasi Indoor - Siti Rofiah; Evita Widiyati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2020)
The education among early childhood does not enough just using speech method, but it also needed the learning aids. The indoor educational aids are playing medium that is designed for the students in learning process either inside or outside class. The aim of making medium is to increase the gross motorskill of students. Therefore, the stimulus should be given to be improve in optimal. The development research is using the seventh steps of Borg and Gall method. The subject of research sample were 30 students about 7 years old in Jombang and the technique of data collection are interview, observation and the instrument of data collection is using questionnair with the data analysis of quantitative. The result of research showed that the approriate indoor of educatinal aids used to increase the gross motorskill among the seventh years old of students which the assessment result from the expert validation of medium about 76% valid or appropriate, the expert validation of content about 78% appropriate. So, the indoor educational aids is appropriate to be implemented to increase the gross motorskill among the seventh years old students and the same age of them.